2018
DOI: 10.1016/j.adaj.2017.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and harms of capnography during procedures involving moderate sedation

Abstract: Adding capnography to standard monitoring of adults during moderate sedation may reduce the risk of developing hypoxemia, increase detection of adverse respiratory events, and is not associated with additional harms. These findings suggest routine use of capnography during moderate sedation has the potential to reduce adverse anesthetic outcomes in dental practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Although much of the literature has recommended the clinical applications of capnography [22,[49][50][51], a scoping review revealed a link between capnography usage and a reduction in serious airway complications in the operating room, ICU, and emergency department and during resuscitation [52]. The 2020 American Heart Association Guidelines for CPR and Emergency Cardiovascular Care emphasize the use of capnography for intubated patients during CPR, and continuous wave-form capnography, along with clinical assessment, remains the most reliable method of confirming and monitoring correct ETT placement [53].…”
Section: Discussionmentioning
confidence: 99%
“…Although much of the literature has recommended the clinical applications of capnography [22,[49][50][51], a scoping review revealed a link between capnography usage and a reduction in serious airway complications in the operating room, ICU, and emergency department and during resuscitation [52]. The 2020 American Heart Association Guidelines for CPR and Emergency Cardiovascular Care emphasize the use of capnography for intubated patients during CPR, and continuous wave-form capnography, along with clinical assessment, remains the most reliable method of confirming and monitoring correct ETT placement [53].…”
Section: Discussionmentioning
confidence: 99%
“…However, various respiratory rate monitoring methodologies have been introduced, such as impedance pneumography (measures respiratory rate via electrodes on the chest wall) [ 9 ], piezoelectric plethysmography, or fiberoptic plethysmography [ 10 ]. However, in clinical practice, capnography, which measures partial pressure of CO 2 , is the generally accepted method for respiratory rate measurement during sedation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial studies, which were exploratory, sought to draw a parallel between dentistry and patient safety 9,10,16,17,18,19,20 . These then gave way to more specific approaches 21,22 , suggesting greater participation by Dentistry in the multidisciplinary approach that the patient safety theme requires.…”
Section: Focus On Patient Safety In Dentistrymentioning
confidence: 99%
“…In order to improve safety in anesthesia, adequate monitoring and a highly trained team were identified as key factors 80,81 . In addition, a systematic review suggested the routine addition of capnography to standard monitoring of adults during moderate sedation 22 .…”
Section: The Solutions Identified and Their Contribution To Improvemementioning
confidence: 99%